Response and growth of some maize varieties (Zea mays L.) at various KNO3 concentrations - Raspowo Hadikusumo Diarjo; Muhammad Farid Badaruddin; Ambo Ala; Sunanto Sunanto; Ahrani Akbar Fachri (Fakultas Pertanian Universitas Ichsan Gorontalo, 2022)
This study aimed to determine the interaction effects of several maize varieties and KNO3 concentrations on maize production. The research was carried out from December 2020 to April 2021 at the Indonesian Cereal Research Institute Facility, Bajeng District, Gowa Regency, South Sulawesi (5°18'21.5